Modeling and Simulation of Fiber Gain Medium - صقور عفيف; ديوب نظير; سعيد جمال; حسن علي (Latakia University Journal -Basic Sciences Series, 2021)
The design and manufacture of laser sources is extremely important for a wide variety of applications such as sensors, spectroscopy, industrial and optical communications applications. The latter has a peculiarity of its importance, as research focuses on designing laser sources with specific specifications that meet the requirements of Wavelength Division Multiplexing - WDM, which forms the backbone for developing and improving the performance of optical networks. The emergence of optical fibers and their rapid development in properties, qualities and the possibility using them as an amplification medium constituted a turning point in the field of solid lasers. This development led to the emergence of a very important field of research: the field of fiber lasers that use single-mode optical fibers as an amplification medium. The research aims and focuses on proposing ways to reach a set of characteristics of a solid fibers gain medium (designed or artificially approved). The technique of achieving the research objective is based on the use of the OptiSystem program, which is used worldwide in both the research and industrial fields, in addition to using the MATLAB program in an assisted simulation process by receiving its data from the OptiSystem semulator. In this research, one type of optical fiber is studied, which is a standard single-mode fiber, but there is the possibility of generalizing the research to arrive at the characteristics of any type of fiber used. By applying the proposed simulation, we can arrive at the properties of the fiber gain medium, most important is the gain of the medium as a function of the wavelength for different pumping powers and different lengths of the studied optical fiber. A new method has been proposed for obtaining the Amplified Spontaneous Emission-ASE, that is to place the fiber within a loop comprising an optical filter whose bandwidth is at least equal to the emission bandwidth of the amplification medium similar to rare earth elements like where the simulation was carried out using OptiSystem software and the validity of the results was compared with reference studies.